Antimycobacterial evaluation of pyrazinoic acid reversible derivatives - Dolezal, Martin; Kesetovic, Diana; Zitko, Jan (Current pharmaceutical design, 2011)
Design, results of in vitro antimycobacterial evaluation, and study of structure-activity relationships of various pyrazinecarboxylic acid reversible derivatives are presented. This review deals with some pyrazinamide analogues/prodrugs derived from Nphenylpyrazine- 2-carboxamides (1), arylaminopyrazine-2,5-dicarbonitriles (2), aryl/alkylsulphanylpyrazines (3,4), and aroylpyrazines (5) effecting >50% inhibition in the primary antimycobacterial screen. The promising pyrazine candidates for further antimycobacterial evaluation were discovered. Results give good view onto structure-activity relationships of these analogues and promise even better activity of new compounds prepared after some structure optimization experiments.
Keywords: viabilita buněk; Cell Line; pyrazinamid; Pyrazinamide; Structure-Activity Relationship; molekulární struktura; antibakteriální látky; Molecular Structure; racionální návrh léčiv; Microbial Sensitivity Tests; Cell Survival; Prodrugs; Mycobacterium; vztahy mezi strukturou a aktivitou; Animals; lidé; Anti-Bacterial Agents; prekurzory léčiv; Humans; zvířata; mikrobiální testy citlivosti; Drug Design; buněčné linie